2013
DOI: 10.1128/cvi.00435-13
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of a 10-Fold-Lower Dose of a Commercial Human Tuberculosis Vaccine, Mycobacterium bovis Bacillus Calmette-Guérin Danish, Induced Levels of Protection against Bovine Tuberculosis and Responses in the Tuberculin Intradermal Test Similar to Those Induced by a Standard Cattle Dose

Abstract: T he human tuberculosis (TB) vaccine, Mycobacterium bovis bacillus Calmette-Guérin (BCG), has been shown to induce a significant level of protection in cattle against bovine TB, caused by M. bovis, in experimental challenge and field trials (1). However, the vaccine has not been used in national bovine TB control programs because cattle, at least in the first year after vaccination, may react positively to the tuberculin intradermal test, and protection may not be complete (2). Recent research showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…This difference in reactivity percentages with our results could be related to the dose and strain used. Similar percentages of TST conversion have been reported in other studies using high vaccine doses between 10 6 -10 8 CFU in humans, wildlife animals, and mouse model (Buddle et al, 2013;Tree et al, 2004). In addition, the protective efficacy reported in those studies was lower in vaccinated animals that showed a strong DTH response to bovine PPD than those animals that did not develop it (Skinner et al, 2001;Ritz et al, 2008).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This difference in reactivity percentages with our results could be related to the dose and strain used. Similar percentages of TST conversion have been reported in other studies using high vaccine doses between 10 6 -10 8 CFU in humans, wildlife animals, and mouse model (Buddle et al, 2013;Tree et al, 2004). In addition, the protective efficacy reported in those studies was lower in vaccinated animals that showed a strong DTH response to bovine PPD than those animals that did not develop it (Skinner et al, 2001;Ritz et al, 2008).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, it is relevant to improve the knowledge of factors determining the development of a delayed type hypersensitivity (DTH) response, if it really develops when vaccine is given under a number of different modalities and stages (Cockle et al, 2002;Logan et al, 2005). Few studies talk about the development of a DTH response or conversion of tuberculin skin test (TST); as a result of the vaccine application, one of this studies demonstrated that DTH reaction is developed in the first months and lost in 90% of the vaccinated animals at nine months post-vaccination (Whelan et al, 2011;Buddle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of reducing both the cost of an oral vaccine and the potential for environmental contamination with BCG, we need to define the minimal efficacious dose for badgers. Given that the effective dose of injected BCG appears to bear no relationship to the size of the target animal—10 equivalent human doses of BCG Danish for badgers (Lesellier et al, 2011) compared to 0.5 equivalent human doses for cattle (Buddle et al, 2013)—these data have to be generated empirically using badgers. The objectives of the two vaccine efficacy studies (VES) reported here were to compare the efficacy of BCG Danish strain in a lipid matrix with unformulated BCG given orally (VES3) at a dose of 10 8 CFU, and to evaluate the efficacy of BCG Danish in a lipid matrix at a 10-fold lower dose than previously evaluated in badgers (VES4).…”
Section: Introductionmentioning
confidence: 99%
“…BCG Danish is a widely used human pediatric vaccine to reduce human TB. Likewise, BCG Danish has been shown to reduce bovine TB disease burden in both experimental and field studies and has a well-established safety profile in cattle ( 1 , 46 , 47 ). The BCG Danish deletion derivatives used in this study are more attenuated and safer than the parental BCG strain in immunocompromised mice [( 48 , 49 ) and Berney-Meyer et al, unpublished data].…”
Section: Introductionmentioning
confidence: 99%